Slang Words used in Olivia Rodrigo Song Lyrics in the Album of Sour - Ayu Retno Adi Pamungkas, Diajeng; Kustantinah, Indri; Himatu K, Rr. Festi (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This final project is based on the study which attempted to analyze the slang word used in song lyrics by Olivia Rodrigo. The song’s album is called Sour. There were eleven songs in the album but the researcher takes only seven among of them. The songs are Brutal, Traitor, Driver License, Good 4 U, Happier, Jealousy-jealousy, and Hope Ur Ok. The main purpose of this study is were to analyze the types of slang words found in the song lyrics, the meaning of the slang words found in song lyrics, and the dominant slang words found in song lyrics. This research is descriptive-qualitative analysis which analyzed the slang word used in the song lyrics usin Allan and Burridge’s theory (2006). The result of the study was there were 48 data of slag words found in the song lyrics. Those slang words was classified into 4 types of slang words. The types were fresh and creative (41.6%), flippant (27.3%), imitative (12.5%), and clipping (18.5%). From these result it can be concluded that the dominant type of slang word is fresh and creatve.